Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Two newly isolated compounds from Hansenia weberbaueriana and their anti-inflammatory potential - Jie Li; Su Hu; Li Huang; Li-Lian Zhao; Li-Jun Huang; Wei-Jun Dong; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Microfluidic investigation on multiphase interaction behavior and carbon dissolution sequestration mechanisms during CO₂ injection in high-water-cut deep reservoirs - Xue Zhang; Qi’an Da; Chenxi Duan; Bin Huang; Cheng Fu; Dian Zhang; Lei Li; Yuliang Su (Chemical Engineering Journal, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Divergent drought-induced suppression on vegetation and associated feedbacks: Satellite-based observations in 2022 across the Yangtze River basin, China - Lei Han; Yanan Chen; Chaoyang Wu; Li Yao; Ying Wang; Chao Su; Xuan Li; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; Xuguang Tang (Journal of Hydrology, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Tree-level carbon stock estimations across diverse species using multi-source remote sensing integration - Qing Li; Jia Yin; Xiaoxin Zhang; Dalei Hao; Matheus Pinheiro Ferreira; Wenhui Yan; Ye Tian; Da Zhang; Shen Tan; Sheng Nie; Tianyu An; Xiaoyao Li; et al. (Computers and Electronics in Agriculture, 2025)

Model tests study of multi-layer geosynthetic-reinforced pile-supported embankments and evaluation of analytical design models - Da Zhang; Guangqing Yang; Ting Li; Peng Xu; Penghui Su (Transportation Geotechnics, 2025)

Inhibition effect of Botrytis cinerea and quality preservation of grape by Bletilla striata polysaccharide - Da Li; Yanli Zheng; Xuemei Han; Haiyu Ji; Xiaoxiang Su; Zhou Yuan; Kejing Yang; Xiaoyu Jia (Physiological and Molecular Plant Pathology, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

Dual carbon isotopes constrain the sources and age variations of terrestrial organic carbon in the middle Okinawa Trough since the last deglaciation - Mengna Chen; Chenglong Su; Shuang Wang; Da-Wei Li; Hailong Zhang; Li Li; Guangxue Li; Bingyuan Xu; Jishang Xu; Meixun Zhao (Global and Planetary Change, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Development of Extubation Success Prediction Model for Mechanically Ventilated Patients with Spontaneous Cerebellar Hemorrhage - Yao Jiang; Yue Yu; Jing Fan; Lei Zhang; Yang Ye; Ying-hong Hu; Li-da Su (The Cerebellum, 2024)

Iron species and sulfur isotopic compositions of authigenic pyrite in deep-sea sediments at southern Hydrate Ridge, Cascadia margin (ODP Leg 204): implications for non-steady-state depositional and diagenetic processes - Chenhui Liu; Shao-Yong Jiang; Xin Su; Xiaopeng Bian; Hai Ding; Da Li; Tao Yang (Frontiers in Marine Science, 2024)
Two accretionary sediment sequences from Sites 1245 and 1252 recovered during Ocean Drilling Program (ODP) Leg 204 at southern Hydrate Ridge were investigated to explore the response of geochemical partitioning of iron and sulfur isotopic composition of authigenic pyrite to non-steady-state depositional and diagenetic scenarios. Five iron species were characterized by a modified sequential extraction procedure that covers almost all iron-bearing minerals in sediment cores, including: (1) iron-bearing carbonates, mainly siderite; (2) ferric (hydr)oxides, probably ferrihydrite and/or lepidocrocite; (3) magnetite; (4) iron-bearing silicates; and (5) pyrite. Highly reactive iron has been accumulated for a long-term steady-state history and its pyritization, to varying degrees, is limited by availability of dissolved sulfide. This causes pyrite and siderite occurred in the same sedimentary layer and shows an inverse relationship between their concentrations. From this, their proportions to highly reactive iron can be chosen for evaluating the degree of sulfidization. A significant change in sulfur isotopic composition of pyrite (-42.4 to +16.8‰ VCDT) indicates that the steady-state conditions are dramatically limited, where the δ 34 S values higher than -20‰ may result from an upward shift of SMT zone close to the seafloor or a sudden, massive depositional event. To explain the downcore sulfidization effects and pyrite δ 34 S values, we developed two categories of conceptual scenarios based on variations in sedimentation rate and methane flux. The geochemical features similar to those derived from each scenario were searched in the sediment columns and the non-steady-state events behind the scenarios were proved to be consistent with the real observations. Thus, iron species and pyrite δ 34 S values can be regarded as a proxy to differentiate different non-steady-state depositional and diagenetic controls on the sedimentary record.

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

A comparative study on the nutritional composition, protein structure and effects on gut microbiota of 5 fermented soybean products (FSPs) - Xinyu Miao; Honghong Niu; Mubai Sun; Xin Dong; Mei Hua; Ying Su; Jinghui Wang; Da Li (Food Research International, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Mitigating life-cycle environmental impacts and increasing net ecosystem economic benefits via optimized fertilization combined with lime in pomelo production in Southeast China - Xiaojun Yan; Yifei Ma; Kunpeng Kong; Muhammad Atif Muneer; Lijun Zhang; Yadong Zhang; Zhihan Cheng; Ziwei Luo; Changcheng Ma; Chaoyuan Zheng; Wenhao Yang; Jiuxin Guo; et al. (Science of The Total Environment, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

A Pore-Scale Model for Electrokinetic In situ Recovery of Copper: The Influence of Mineral Occurrence, Zeta Potential, and Electric Potential - Kunning Tang; Zhe Li; Ying Da Wang; James McClure; Hongli Su; Peyman Mostaghimi; Ryan T. Armstrong (Transport in Porous Media, 2023)
Electrokinetic in-situ recovery is an alternative to conventional mining, relying on the application of an electric potential to enhance the subsurface flow of ions. Understanding the pore-scale flow and ion transport under electric potential is essential for petrophysical properties estimation and flow behavior characterization. The governing physics of electrokinetic transport is electromigration and electroosmotic flow, which depend on the electric potential gradient, mineral occurrence, domain morphology (tortuosity and porosity, grain size and distribution, etc.), and electrolyte properties (local pH distribution and lixiviant type and concentration, etc.). Herein, mineral occurrence and its associated zeta potential are investigated for EK transport. The new Ek model which is designed to solve the EK flow in complex porous media in a highly parallelizable manner includes three coupled equations: (1) Poisson equation, (2) Nernst–Planck equation, and (3) Navier–Stokes equation. These equations were solved using the lattice Boltzmann method within X-ray computed microtomography images. The proposed model is validated against COMSOL multiphysics in a two-dimensional microchannel in terms of fluid flow behavior when the electrical double layer is both resolvable and unresolvable. A more complex chalcopyrite-silica system is then obtained by micro-CT scanning to evaluate the model performance. The effects of mineral occurrence, zeta potential, and electric potential on the three-dimensional chalcopyrite-silica system were evaluated. Although the positive zeta potential of chalcopyrite can induce a flow of ferric ion counter to the direction of electromigration, the net effect is dependent on the occurrence of chalcopyrite. However, the ion flux induced by electromigration was the dominant transport mechanism, whereas advection induced by electroosmosis made a lower contribution. Overall, a pore-scale EK model is proposed for direct simulation on pore-scale images. The proposed model can be coupled with other geochemical models for full physicochemical transport simulations. Meanwhile, electrokinetic transport shows promise as a human-controllable technique because the electromigration of ions and the applied electric potential can be easily controlled externally. Graphical abstract

Transcriptome sequencing reveals the senescence mechanism of ethylene-insensitive cut Rhododendron flowers - Shi-da Xu; Fang Zheng; Xing-min Geng; Zhi-li Jiang; Ling-feng Mao; Jia-le Su (Postharvest Biology and Technology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

Correction: Sepsis Impairs Purkinje Cell Functions and Motor Behaviors Through Microglia Activation - Yue Zhao; Yao Jiang; Ying Shen; Li-Da Su (The Cerebellum, 2023)

Sepsis Impairs Purkinje Cell Functions and Motor Behaviors Through Microglia Activation - Yue Zhao; Yao Jiang; Ying Shen; Li-Da Su (The Cerebellum, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Evaluating the survival of Aspergillus niger in a highly polluted red soil with addition of Phosphogypsum and bioorganic fertilizer - Lingzi Meng; Shang Pan; Limin Zhou; Choochad Santasup; Mu Su; Da Tian; Zhen Li (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

PQBP1: A New Player in Metabotropic Glutamate Receptor Signaling and Synaptic Plasticity - Li-Da Su; Ying Shen (Neuroscience Bulletin, 2021)

Implantation of Bone Marrow Mesenchymal Stem Cells into Small Intestinal Submucosa Improves Bile Duct Injury in Rabbits - Ying Li; Piao Wang; Xiao-dong Hu; Jing-da Zeng; Cheng Fang; Yu Gan; Fang-yi Peng; Xiao-li Yang; De Luo; Bo Li; Song Su (Tissue Engineering and Regenerative Medicine, 2021)

Endoplasmic Reticulum Stress Regulates Cardiomyocyte Apoptosis in Myocardial Fibrosis Development via PERK-Mediated Autophagy - Changjiang Zhang; Yuanhong Li; Jingbo Zhao; Ke Su; Ke He; Yurong Da; Hao Xia (Cardiovascular Toxicology, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Remediation of lead-contaminated water by geological fluorapatite and fungus Penicillium oxalicum - Da Tian; Wenchao Wang; Mu Su; Junyi Zheng; Yuanyi Wu; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Science and Pollution Research, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Synthesis and antiproliferative properties of novel naringenin derivatives - Su-You Liu; Jiang Zeng; Kun-Jian Peng; Li-Chao Zhang; Li-Jun Liu; Zhi-Yong Luo; Da-You Ma (Medicinal Chemistry Research, 2017)

Analysis on shear wave velocity structure of a gravel landslide based on dual-source surface wave method - Xing-qian Xu; Li-jun Su; Guang-da Zhang; Hong-hu Zhu (Landslides, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Downregulation of Glutamate Transporter EAAT4 by Conditional Knockout of Rheb1 in Cerebellar Purkinje Cells - Nan-Wei Jiang; De-Juan Wang; Ya-Jun Xie; Liang Zhou; Li-Da Su; Huashun Li; Qin-Wen Wang; Ying Shen (The Cerebellum, 2016)

Qualitative and Semiquantitative Analysis of Fecal Bifidobacterium Species in Centenarians Living in Bama, Guangxi, China - Fang Wang; Guohong Huang; Da Cai; Danlei Li; Xiaolin Liang; Ting Yu; Peihong Shen; Haiyan Su; Jidong Liu; Hongcang Gu; Mouming Zhao; Quanyang Li (Current Microbiology, 2015)

LGI1 is Involved in the Development of Mouse Brain - Li-Da Su; Ya-Jun Xie; Liang Zhou; Ying Shen; Ying-Hong Hu (The Cerebellum, 2015)

Expressions of ER, PR, HER-2, COX-2, and VEGF in Primary and Relapsed/Metastatic Breast Cancers - Li Sun; Da-hai Yu; San-Yuan Sun; Shi-Chao Zhuo; Su-sheng Cao; Ling Wei (Cell Biochemistry and Biophysics, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Retrograde cPLA2α/Arachidonic Acid/2-AG Signaling Is Essential for Cerebellar Depolarization-Induced Suppression of Excitation and Long-Term Potentiation - Li-Da Su; De-Juan Wang; Dong Yang; Ying Shen; Ying-Hong Hu (The Cerebellum, 2013)

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells - Na Zou; Xiao Wu; Yan-Yan Jin; Meng-Zao He; Xin-Xin Wang; Li-Da Su; Marjan Rupnik; Zhen-Yong Wu; Li Liang; Ying Shen (The Journal of Membrane Biology, 2013)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Cerebellar Long-term Depression is Deficient in Niemann–Pick Type C Disease Mice - Cheng-Long Sun; Li-Da Su; Qiong Li; Xin-Xin Wang; Ying Shen (The Cerebellum, 2011)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)